Medication supply for people evacuated during disasters. Issue 1 (February 2015) - Ochi, Sae; Hodgson, Susan; Landeg, Owen; Mayner, Lidia; Murray, Virginia
Abstract: Medication loss is a major problem in disaster settings, and it is crucial for patients to bring their medication and healthcare items with them when they leave their homes during an evacuation. This article is based on a systematic literature review on medication loss, the objectives of which were to identify the extent and implications of medication loss, to identify the burden of prescription refill, and to make recommendations on effective preparedness. The review revealed that medication loss, prescription loss and refills, and the loss of medical aids are a significant burden on the medical relief teams. The medical aids are not limited to drugs, but include routine medications, medical/allergy records, devices for specific care and daily life, and emergency medications. One possible solution is to make a personal emergency pack and for people to carry this with them at all times. To ensure that patients are adequately prepared, stakeholders, especially health professionals, need to be actively involved in the preparation plans. Since our findings have little impact on disaster risk reduction unless shared broadly, we are now taking actions to spread our findings, such as presenting in conferences and via posters, in order to raise awareness among patients and healthcare professionals. As part of these activities, our findings were presented at the Evidence Aid Symposium on 20 September 2014, at Hyderabad, India.